Penerapan Association Rules - Market Basket Analysis untuk Mencari Frequent Itemset dengan Algoritma FP-Growth - Cut Rizki Artsitella; Amrina Rosyada Apriliani; Septi Ashari (Universitas Al Azhar Indonesia, 2021)
In retail stores, product variations and prices are the main attraction. Products with many discounts are the most sought-after products. The promotion itself requires a special method for determining the discount. The layout in supermarkets is also something that retail stores need to pay attention to. One method that can be used to determine the product layout, promo for each product is Market Basket Analysis. The purpose of this research is to determine associative relation that occurs between items and to find out the solution to the problem of layout arrangement, catalog creation, and determination of shopping vouchers in Gading Mas Swalayan 1 based on the output of Rapid Miner software. Based on the output results obtained 7 associative relationships that have a lift ratio value > 1 and it can be seen the determination of the layout of the item, catalog, and shopping voucher form. Layout changes are made for the comfort and convenience of consumers in taking the products they need and cataloging is determined by combining frequently purchased products with products that are rarely purchased. And the making of shopping vouchers is used to provide discounted prices where this is to reduce inventory and attract consumers.Keywords – Market Basket Analysis, Rapid Miner, Retail, The relation of associative